Understanding phase-change materials with unexpectedly low resistance drift for phase-change memories. Issue 13 (16th March 2018) - Li, Chao; Hu, Chaoquan; Wang, Jianbo; Yu, Xiao; Yang, Zhongbo; Liu, Jian; Li, Yuankai; Bi, Chaobin; Zhou, Xilin; Zheng, Weitao
Abstract : There is an increasing demand for high-density memories with high stability for supercomputers in this big data era. Abstract : There is an increasing demand for high-density memories with high stability for supercomputers in this big data era. Traditional dynamic random access memory cannot satisfy this requirement due to its limitation of volatile and power-consumable data storage. Multi-level cell phase-change memory (MLC PCM) based on phase-change materials possesses a higher storage density, and is considered to be the most promising candidate. However, a detrimental resistance drift exists commonly in phase-change materials, and it destroys the stability and greatly limits the development of MLC PCM. Here, we propose a completely new strategy to suppress resistance drift by exploring its microscopic mechanism via combinations of theoretical calculations and experiments. We have found, for the first time, that resistance drift originates from the change in electron binding energy induced by structural relaxation and is proportional to the reciprocal of the dielectric coefficient according to the hydrogen-like model. On this basis, we propose to reduce the resistance drift by increasing the thermal stability of the dielectric coefficient. Two series of experiments prove the effectiveness of our new strategy. The resistance drift exponent of phase-change films is significantly reduced to 0.023 using our strategy, which is lower by half than the best result (0.050) reported previously. Interestingly, the films also show improved storage properties. These results not only unravel the fact that the stability and storage function of phase-change films can be simultaneously improved by modification of dielectric properties but also pave the way for future material design for stable MLC PCM.